Antinociceptive effect on mice of the hydroalcoholic fraction and (-) epicatechin obtained from Combretum leprosum Mart & Eich - L.S. Lopes (Brazilian Journal of Medical and Biological Research, 2010)
Previous studies on Combretum leprosum, a tree growing in the Northeastern states of Brazil, have shown antinociceptive effects of the ethanol extract of its leaves and bark, but studies examining its constituents are rare. The objective of this study was to evaluate the antinociceptive effect of the hydroalcoholic fraction (HF) of one of its constituents, the flavonoid (-) epicatechin (EPI), administered orally to mice (20-30 g) in models of chemical nociception, and the possible mechanisms involved. Different doses of HF (62.5 to 500 mg/kg) and EPI (12.5 to 50 mg/kg) were evaluated in models of abdominal writhing, glutamate, capsaicin, and formalin in animals pretreated with different antagonists: naloxone, ondansetron, yohimbine, ketanserin, pindolol, atropine, and caffeine in the abdominal writhing test. To determine the role of nitric oxide, the animals were pretreated with L-arginine (600 mg/kg, ip) in the glutamate test. The HF was effective (P < 0.05) in all protocols at different doses and EPI was effective in the abdominal writhing, capsaicin and glutamate tests (P < 0.05) at doses of 25 and 50 mg/kg. However, in the formalin test it was only effective in the second phase at a dose of 25 mg/kg. The antinociceptive effect of HF was inhibited when HF was associated with yohimbine (0.15 mg/kg), ketanserine (0.03 mg/kg), and L-arginine (600 mg/kg), but not with the other antagonists. HF and EPI were effective in models of chemical nociception, with the suggested participation of the adrenergic, serotonergic and nitrergic systems in the antinociceptive effect of HF.